Genomic privacy and limits of individual detection in a pool - Sankararaman, Sriram; Obozinski, Guillaume; Jordan, Michael I; Halperin, Eran (Nature genetics, 2009)
David Craig and colleagues recently reported methods allowing detection of individual genotypes from summary data of high-density SNP arrays. Eran Halperin and colleagues now report analyses of the statistical power of these methods, employing likelihood ratio statistics to provide an upper-bound to the limits of detection. Recent studies have demonstrated that statistical methods can be used to detect the presence of a single individual within a study group based on summary data reported from genome-wide association studies (GWAS). We present an analytical and empirical study of the statistical power of such methods. We thereby aim to provide quantitative guidelines for researchers wishing to make a limited number of SNPs available publicly without compromising subjects' privacy.